Synthesis of benzoxazole - YUDONG HUANG; XIANGQUN CHEN (2005)
Synthesis method for benzo oxazole diamine, which involves organic compound synthesis process. Said p-phenylene-2,2'-bis (5-aminobenzo oxazole) of the present invention is prepared as follows: a. Formulate phosphoric acid and P2O5 into ploy(phosphoric acid) solution; b. Add to the resulting solution 2,4-diamiophenol hydrochloride and terephthalic acid; c. Add then reducing agent SnCl2; d. Followed by neutralization, extraction and drying, then the primary product is obtained; e. Subject the primary products to extraction and drying to get bright yellow powder. And said 2,6-bis primary product to extraction and drying to get bright yellow powder. And said 2,6-bis primary product to extraction and drying to get bright yellow powder. And said 2,6-bis primary product to extraction and drying to get bright yellow powder. And said 2,6-bis primary product to extraction and dyring to get bright yellow powder. And said 2,6-bis (p-aminobenzyl) benzo [1,2-d; 5,4-d'] dioxazole is prepared as follows: a. Formulate phosphoric acid and P2O5 into ploy(phosphoric acid) solution; b. Add to the resulting solution 4,6-metaphenylene diamine hydrochloride and p-aminobenzoic acid.